Determinants of Acceptance and Non -Acceptance of Tattoo and Body Piercing among Youths: Universities in Ogun State: A Case of Federal University of Agriculture, Abeokuta - A.M., Mojeed; M. O., Oose (Journal of Home Economics Research, 2024)
This study focused on tattoo and body piercing among youths in tertiary institutions in Ogun State, Nigeria. Specifically, the study determined youths’ awareness of body parts for the placement of tattoos and body piercing, factors influence youth’s acceptance of tattoos and body piercing and factors that influence youths’ non-acceptance of tattoos and body piercing. The area of the study was Ogun State. Population was made up of undergraduates of Federal University of Agriculture, Abeokuta, Ogun State. Data were obtained through questionnaire. Frequency counts and percentages were used for data analysis. Findings include 13 body parts were tattoo and body piercing are placed. These include hand (91.8%), leg (88.2%), nose (93.6%) navel (76.4%), among others. Other major findings include a major factor (Maf) that influencing youths’ acceptance of tattoos and body piercing, namely, “Interest” with percentage score of (58.2%). Further, there are eight (8) major factors that influences youths’ non- acceptance of tattoos and body piercing. These include; risk of disease (82.7%), risk of infection (66.4%), not interested (79.1%), it is difficult to remove (70.9%), and others. Based on the findings it is recommended that sensitization and educative awareness should be made available in various tertiary institutions on health and disease related risks associated with tattoos and body piercing.